Lompat Kodok: Modifikasi Lompat Kangkang Berbasis Permainan untuk Anak Sekolah Dasar - Emayanti Anggraeni; Mukharrar Fadjri; Faida Musa’ad; La Robi (Kilau Publishing, 2025)
To determine the effect of gender variables (male vs. female) and participation in team sports (individual sports vs. other sports (team sports)). Statistical analysis of data was performed using one-way ANOVA. Data normality was evaluated using KS and QQ plots. Levene's test was used to evaluate variance homogeneity. Missing data in the dependent variable was taken into account, so surveys with missing values were excluded. All data were analyzed using SPSS version 22. Results are reported as mean ± standard deviation and a significance level of 0.05.